Characteristics of human papillomaviruses infection in men with genital warts in Shanghai - Chen, Xiaogang (Oncotarget, 2016)
Human papillomaviruses (HPV) infected men causes continued transmission of HPV to women. The prevalence of 15 high-risk HPV strains (HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66 and 68) and 6 low-risk HPV strains (HPV6, 11, 42, 43, 44 and CP8304) were evaluated in 935 males with genital warts. Of the 447 (447/935, 47.8%) HPV DNA positive subjects, 230 (24.6%), 356 (38.1%) and 139 (14.9%) were infected by high-risk, low-risk and both high and low-risk HPV respectively. Of the 356 low-risk HPV infected subjects, 333(93.5%) were infected by single HPV strain; 203 (57.0%), 147 (41.3%), 24 (6.7%) and 5 (1.4%) were infected with HPV genotype 6, 11, CP8304 and 44 respectively; population with age ≤ 20 showed the highest infection rate. High-risk HPV are also highly prevalent in our patients, genotype 16, 58, 51, 39, 52 and 53 are the top five prevalent genotypes with infection rates of 27.4%, 18.7%, 14.3%, 13.9%, 12.6% and 12.6% respectively; only 68.3% subjects were sole infection; subjects with 41 ≤ age ≤ 50 showed the highest infection rate. Both high and low-risk HPV are highly prevalent in men with genital warts, its impact on women HPV control and prevention need further evaluation.